Understanding collaborative language learning in novice-level foreign language classrooms: perceptions of teachers and students. Issue 2 (17th February 2018) - Sun, Peijian (Paul); Yuan, Rui (Eric)
ABSTRACT: This study explored the congruence and disparities among three groups of foreign language (Chinese, French, and German) students' and teachers' perceptions of collaborative/cooperative language learning (CLL) strategies in novice-level classroom contexts. A total of 168 participants from a university in the USA took part in this mixed-method study. The quantitative findings from a 10-item CLL questionnaire suggested that while the students' and teachers' perceptions of CLL strategies were generally consistent and positive, some disparities emerged in terms of their perceptions towards pair work, 3–6 as a group work, interview, and role playing . The qualitative findings from interviews and classroom observations provided some possible explanations to the differences discovered. The quantitative findings also revealed that foreign language type was not a factor differentiating students' and teachers' perceptions of CLL strategies. Some practical implications are provided for the effective implementation of CLL strategies in novice-level foreign language classrooms.